Upaya Meningkatkan Partisipasi Pemilih Pemula dalam Pemilihan Kepala Daerah di Wilayah Perbatasan Kabuputen Belu - Sae, Donatus; Adeo Dato J. B. Mbiri; Petrus A. G. Taek; Joseph F. Bere (Journal of Mandalika Literature, 2025)
Efforts to increase the participation of novice voters are against the problem of data on the number of young voters which reaches 70-80 million out of 93 million people. Research shows that young people's interest in politics is only 1.1%. This is a problem that threatens the sustainability of electoral democracy. This study aims to find out the reasons for the low voter participation at SMAN 2 Tasbar, Belu Regency and seeks to provide stimulation to build awareness of novice voters to participate in the regional head elections of Belu Regency and East Nusa Tenggara Province for the 2024-2025 period. The methods used in this study are observation and interviews.